Introducing the Egypt Labor Market Panel Survey 2018 - Caroline Krafft; Rāǧī Asʿad; Khandker Wahedur Rahman (IZA Journal of Development and Migration, 2021)
This paper introduces the 2018 wave of the Egypt Labor Market Panel Survey (ELMPS), previously fielded in 1998, 2006, and 2012. The ELMPS has already become the primary source of data for a large number of scholarly and policy studies on the labor market and human development issues in Egypt, and this new wave will further enhance its value as a critical data public good. This longitudinal survey is nationally representative, tracking both households and individuals over two decades. In this paper, we describe the key characteristics of the 2018 wave, including sampling, fielding, and questionnaire design. Changes in the collection of retrospective data starting in 2018 are discussed, and we demonstrate that they improved the data quality. We examine the patterns of attrition and present the construction of weights designed to correct for attrition, as well as to ensure that the sample remains nationally representative. We compare the ELMPS data with other Egyptian data sources, namely, the 2017 Census and various rounds of the Labor Force Survey (LFS). The data provide important new insights into Egypt's labor market, economy, and society.
Keywords: J00; C81; C83; 330; survey; panel data; public use data; sample weights; labor market; Egypt